Post-Disaster Homelessness: The 6th February 2023 Turkey Earthquake and Malatya Case - Hüseyin Taşlı (İstanbul Üniversitesi Sosyoloji Dergisi)
One of the structural causes of homelessness is natural disasters. As a result of such events, some individuals who had housing prior to the disaster become homeless, while places like parks and streets, where the chronically homeless often reside, are also damaged along with the city as a whole. Although a limited number of studies on “post-disaster homelessness” exist in the international literature, no research has been conducted on this phenomenon in Türkiye. The earthquakes of February 6, 2023, affected eleven cities, leaving many people homeless after their houses were destroyed or severely, moderately, or lightly damaged. Most of the homeless earthquake victims were initially placed in tent cities and later in container cities. These container cities provided temporary shelter for earthquake victims, effectively postponing the onset of homelessness. However, in Malatya—one of the cities affected by the earthquake—a group of homeless individuals emerged who were unable to settle in container city areas. This was due to issues such as problems stemming from private property ownership, houses rented without formal contracts, disruptions caused by public institutions, low incomes, and rising rents. As a result, these individuals sought refuge in a tent that provided collective shelter. During this process, many earthquake victims who had initially sheltered in this tent left as they found alternative housing. However, those who lacked such opportunities and continued to stay in the tent became examples of post-earthquake homelessness. As part of this qualitative research, interviews were conducted with two distinct groups: six temporarily homeless individuals who became homeless after the earthquake and four chronically homeless individuals who had already been homeless before the disaster. The data obtained from these two groups were compared and analyzed, revealing significant differences between the chronic and temporary homeless in terms of reasons for homelessness, gender, income, education, criminal record, addiction, level of personal care, work tendencies, services needed, social relationships, and discourse.